The Revd. Dr. Stephen Hales, F.R.S. - Thornton, Robert John, 1768?-1837 (1800)
Portrait of The Revd. Dr. Stephen Hales, F.R.S., author of Vegetable Statics, with a view below of a Greek temple with a plant inside a bell jar on top of a column. Drawn by Coates R. A. Engraved by Hopwood. London: Published by Dr. Thornton. Part of a group of 16 portraits of noted botanists.